Let p , q and r be the zeros of the polynomial x 3 + 5 x 2 − 4 x + 3 .
Find the value of p 2 q + p 2 r + q 2 p + r 2 p + q 2 r + r 2 q .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Good work, I was going to upload the same solution but you won me.
did the same! overrated!
same approach but got pretty big equations
p 2 q + p 2 r + q 2 p + r 2 p + q 2 r + r 2 q = p q ( p + q ) + q r ( q + r ) + r p ( r + p )
= p q ( p + q + r ) − p q r + q r ( p + q + r ) − p q r + r p ( p + q + r ) − p q r
= ( p + q + r ) ( p q + q r + r p ) − 3 p q r
Using Vieta's Formulas, we have: p + q + r = − 5 , p q + q r + r p = − 4 and p q r = − 3 .
Therefore,
p 2 q + p 2 r + q 2 p + r 2 p + q 2 r + r 2 q = ( p + q + r ) ( p q + q r + r p ) − 3 p q r
= ( − 5 ) ( − 4 ) − 3 ( − 3 ) = 2 0 + 9 = 2 9
Through Vieta you can see that
q + p + r = − 5 q r + p q + p r = − 4 p q r = − 3
Now, through newton sums,
p 3 + q 3 + r 3 = − 1 9 4
You will see why it is necessary. Let the equation that is needed to be evaluate for this question be Q
Now,
( q + p + r ) 3 = ( p 3 + q 3 + r 3 ) + 3 ( Q ) + 6 ( p q r )
So,
Q = 3 ( q + p + r ) 3 − 6 ( p q r ) − ( p 2 + q 2 + r 2 )
Substituting the values above, we get:
Q = 3 − 1 2 5 + 1 8 + 1 9 4 = 2 9
I came across this problem when trying to solve another problem.
We're to find p 2 ( − 5 − p ) + q 2 ( − 5 − q ) + r 2 ( − 5 − r ) = ( − ( S 3 + 5 S 2 ) ; whence we can directly apply Newton's Sums at S 3 , getting S 3 + 5 S 2 − 4 S 1 + 9 = 0 , and our answer is 2 9 .
Log in to reply
Oh..... I did not catch that one
I too did the same manipulation SG
Let the polynomial be P ( x ) .
Adding 2 p q r = − 6 , the expression becomes ( p + q ) ( q + r ) ( r + p ) = ( − 5 − p ) ( − 5 − q ) ( − 5 − r ) = P ( − 5 ) = 2 3 hence the answer is 2 3 − ( − 6 ) = 2 9 .
Oops, I just brute forced the solution:
{ p , q , r } = x /. Solve [ x 3 + 5 x 2 − 4 x + 3 = 0 ]
{ 3 1 ( − 3 7 3 5 1 1 − 3 6 5 0 1 2 − 3 2 1 ( 5 1 1 − 3 6 5 0 1 ) − 5 ) , 6 1 ( 1 + i 3 ) 3 2 1 ( 5 1 1 − 3 6 5 0 1 ) − 3 5 + 3 2 2 / 3 3 5 1 1 − 3 6 5 0 1 3 7 ( 1 − i 3 ) , 6 1 ( 1 − i 3 ) 3 2 1 ( 5 1 1 − 3 6 5 0 1 ) − 3 5 + 3 2 2 / 3 3 5 1 1 − 3 6 5 0 1 3 7 ( 1 + i 3 ) }
FullSimplify [ p 2 q + p 2 r + p q 2 + p r 2 + q 2 r + q r 2 ]
2 9
Using Vieta's Formulas p + q + r = − 5 p q + p r + q r = − 4 − p q r = 3
Then ( p + q + r ) ( p q + p r + q r ) = − 5 × − 4 p 2 q + p 2 r + q 2 p + r 2 p + q 2 r + r 2 q + 3 p q r = 2 0 p 2 q + p 2 r + q 2 p + r 2 p + q 2 r + r 2 q + 3 p q r − 3 p q r = 2 0 + 9 p 2 q + p 2 r + q 2 p + r 2 p + q 2 r + r 2 q = 2 9
The expression is actually equal to ( p + q + r ) ( p q + p r + q r ) − 3 p q r and by Vieta, p + q + r = − 5 p q + p r + q r = − 4 p q r = − 3 substituting will give us − 5 × − 4 + ( − 3 × − 3 ) = 2 0 + 9 = 2 9
Problem Loading...
Note Loading...
Set Loading...
Through Vieta you can see that .
p + q + r = − 5 p q + q r + r p = − 4 p q r = − 3 T h e e x p . = p q ( p + q ) + q r ( q + r ) + r p ( r + p ) ⟹ T h e e x p . = p q ( − 5 − r ) + q r ( − 5 − p ) + r p ( − 5 − q ) ⟹ T h e e x p . = − 5 ( p q + q r + r p ) − 3 p q r i m p l i e s T h e e x p . = − 5 ∗ ( − 4 ) − 3 ∗ ( − 3 ) = 2 9